PENGARUH PERSEPSI KEMANFAATAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP PENGGUNAAN LAYANAN APLIKASI GOFOOD - Rusminah Rusminah; Hilmiati Hilmiati (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The Research is conducted to find out perceived usefilness and perceived ease of use to use toward the using of GoFood application at consumers' in Mataram city. This type of research is an associate study. The population in this research is Mataram city comminity that uses GoFood application, with a sample of 100 responden. Sample technique use Non probability samplig with Purposive sampling method. The data-collection techniques used, angket and documentation. The data analysis technique which is applied to examine the hypothesis is double linear regression. The research result shows that there is a positive influence and significant of perceived usefulness and petceived ease of use toward the using of GoFood application at consumers’ in Mataram city, hence it is recommended to Gojek workers to make more impact on services and security and to continue recovery by promoting technological ease, enabling consumers to interact more easily, conveniently and safely.